2006
DOI: 10.1016/j.maturitas.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary alternatives to plant estrogens for menopause

Abstract: Objectives-Every year, millions of women begin the peri-menopause and may experience a number of symptoms related to this transition. Many women are reluctant to use exogenous hormone therapy for treatment of menopausal symptoms and are turning to botanical and dietary supplements (BDS) for relief. This paper reviews the literature on alternatives to plant estrogens for relief of menopausal symptoms.Methods-The MEDLINE database was searched for clinical trials of non-estrogenic plant extracts for menopausal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 65 publications
0
38
0
4
Order By: Relevance
“…Differences in findings across studies of the same product may be due to less than optimal trial design, variation in products and composition of products used, inadequate dosing, the length of treatment and small population size. Furthermore, any therapy claiming to reduce hot flushes should be assessed in blinded trials as placebo effects are high 54 . Furthermore, the placebo effect In our studies were high demonstrating the person's anticipation that an intervention will help them, and these effects should be considered in alternative therapies 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in findings across studies of the same product may be due to less than optimal trial design, variation in products and composition of products used, inadequate dosing, the length of treatment and small population size. Furthermore, any therapy claiming to reduce hot flushes should be assessed in blinded trials as placebo effects are high 54 . Furthermore, the placebo effect In our studies were high demonstrating the person's anticipation that an intervention will help them, and these effects should be considered in alternative therapies 55 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that compounds which are able to interact with hormonal function can have great potential to relieve hormonodependent related diseases (Saunier et al, 2011;Rashed et al, 2014). Many results claimed that plant extract with estrogenic activities can be used for management of menopausal symptoms (Geller and Studee, 2006;Xu et al, 2014). Furthermore, treatment with potential to decrease androgen hormone action is a good candidate for prostate disorders management (Grant and Ramasamy, 2012).…”
Section: Labcmentioning
confidence: 99%
“…The World Health Organization estimated that 1.2 billion women would be 50 years or older by the year 2030 (1). Estrogen decline during menopause may cause various problems such as vasomotor instability, lowered psychometric functions, vaginal and urinary infections, and forgetfulness (2).…”
Section: Introductionmentioning
confidence: 99%